The multicultural experiences, attitudes and efficacy perceptions among prospective teachers - Sıddık Bakır (International Journal of Evaluation and Research in Education (IJERE), 2020)
The purpose of this study is to investigate the concepts of multiculturalism and multicultural education and the multicultural experiences, attitudes and efficacies of prospective teachers of Turkish based on different variables. The study was carried out with a total of 249 prospective teachers of which 77% were female, and 23% were male who were receiving education in the spring semester of the academic year of 2018-2019 at the department of Turkish education of a state university. The study utilized the Multicultural Efficacy Scale. The data were analyzed by utilizing statistics and statistical techniques such as percentages, frequencies, arithmetic means, standard deviations, t-test and one-way analysis of variance. The Cronbach’s Alpha reliability coefficient that was calculated for this study was .868. Based on the findings of the study, it was determined that the prospective Turkish teachers had above-average and positive efficacies towards multicultural education, the saw themselves capable in the “experience, attitude and self-efficacy” dimensions, their perception levels were high, and among different variables, there were significant differences in their multicultural efficacy levels based on the variables of class and place of residence.